Polycystic Ovary Syndrome and Cardiovascular Risk - Madeline Moore; Rahim Hirani; Samy Khessib; Amala P. Chirumamilla; William H. Frishman; Mill Etienne (Cardiology in Review, 2026)
Polycystic ovary syndrome (PCOS) affects an estimated 11–13% of reproductive-age women worldwide and is increasingly recognized as a condition with significant cardiometabolic abnormalities, beyond its reproductive manifestations. This focused narrative review synthesizes contemporary evidence on the mechanistic, subclinical, and clinical links between PCOS and cardiovascular disease. We examine how hyperandrogenism may contribute to insulin resistance and related abnormalities, including dyslipidemia, hypertension, metabolic dysfunction-associated steatotic liver disease, and endothelial dysfunction, which collectively may increase atherosclerotic risk. Chronic low-grade inflammation and sympathetic overactivation are identified as additional, body mass index-independent amplifiers of this risk. Subclinical markers of vascular dysfunction, including increased carotid intima-media thickness, elevated coronary artery calcium, and elevated biomarkers such as asymmetric dimethylarginine and plasminogen activator inhibitor-1, are consistently elevated in women with PCOS relative to controls. A 2024 meta-analysis of over 300,000 women with PCOS demonstrates pooled odds ratios of 2.50 for myocardial infarction and 1.71 for stroke. Importantly, cardiovascular risk is not limited to women with elevated body mass index; lean women with PCOS carry a substantial and underappreciated metabolic burden. Current risk stratification tools inadequately account for PCOS, and cardiology guidelines have not yet formally designated PCOS as an atherosclerotic cardiovascular disease risk-enhancing condition. We review guideline-based cardiovascular risk assessment and interventions that improve cardiometabolic risk factors, including lifestyle modification, metformin, statins, and glucagon-like peptide-1 receptor agonists. Lastly, we identify priority areas for future research in this underserved population.